2012
DOI: 10.4236/jwarp.2012.48067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use and Aquatic Plants on the Water Quality of the Sub-Tropical Alpine Wetlands in India: A Case Study Using Neuro-Genetic Models

Abstract: The suspended and dissolved waste in the incoming storm water of wetlands largely depends on the adjacent land use which can influence the quality of the water body. The micro-and macro-floral population of a wetland can absorb, convert, transform and release different organic or inorganic elements, which can also change or impact the overall quality of the wetland water. The present study investigates the influence of the land use and the plant species in the waterbed on the water quality of a high-altitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Wetlands are versatile ecosystems that provide ecosystem services necessary for the social and economic wellbeing of the local communities living near or around wetlands (Roy et al 2012).…”
Section: Water-related Ecosystem Services Of Wetlandmentioning
confidence: 99%
“…Wetlands are versatile ecosystems that provide ecosystem services necessary for the social and economic wellbeing of the local communities living near or around wetlands (Roy et al 2012).…”
Section: Water-related Ecosystem Services Of Wetlandmentioning
confidence: 99%
“…The suspended and dissolved waste in the incoming storm water of wetlands largely depends on the adjacent land use which can influence the quality of the water body. The estimation capabilities of neuro-genetic models were utilized to identify the inherent relationships between the BOD, DO, Cl and COD with the land use and wetland zoology (Roy et al , 2012b. Samal et al (2011) studied the limnological monitoring during a year and they found that the lake was highly eutrophic with low DO values and high concentrations of BOD, COD, nitrate, phosphate and heavy metal concentration as observed from the sludge sample.…”
Section: Introductionmentioning
confidence: 99%